PENGARUH BAHAN BAKU TERHADAP PRODUKSI INDUSTRI MEBEL DI KOTA PEKANBARU - Halim, Irsyadul; Jahriza, Jahriza; Isbah, Ufira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted in Pekanbaru City, this study aims to find out the problem of furniture industry in the supply of raw materials and know the groove of raw material inventory to the production of furniture industry in Pekanbaru City. Sampling using this census technique because the population number sebayak 22 industries where the population is less than 100 so that the sample is the whole pepulasi. The method of analysis used in this research is descriptive method. Where this study only describes the state of the furniture industry associated with the provision of raw materials in Pekanbaru City. The results of the research that the problem often faced in the provision of raw materials is bad weather, due to bad weather then the condition of roads or road access to bring wood raw materials is also hampered as a result will be delayed arrival of goods, flow of raw material inventory to the production of furniture industry in Pekanbaru is the first plot of the woodcutter in the forest, The price difference of timber from loggers to timber collectors is around Rp.500.000- Rp.2.500.000 / m3, and the price difference of timber from collectors to wood furniture industries ranges from Rp.300.000 - Rp. 700,000 / m3. The scarcity of some timber species has resulted in some expensive timber prices, since collectors sell some of their timber out of town, which is why timber prices are expensive to the wood furniture industry in Pekanbaru.Keywords : Production, Raw Materials, Furniture Industry